Correction of the effects of carbon dioxide and hydrogen sulfide on electrostatic cell monitors measurements of radon in water. Issue 1 (February 2022) - Begy, Robert-Csaba; Savin, Codrin-Fabian; Timar-Gabor, Alida
Abstract: The present study shows that the presence of hydrogen sulfide and carbon dioxide in water have a negative effect on the accuracy of radon measurements in samples when an electrostatic ion collector device (RAD7) is used.CO2 concentrations between 0.65 g/l and 5.19 g/l were generated in water samples containing 222 Rn activities ranging from 23.4 ± 0.9 Bq/l to 6.7 ± 0.9 Bq/l, after which the samples were measured by a RAD7 device, and the results compared to the radon activity values of the gas-free samples. The same procedure was followed for H2 S concentrations from 0.125 mg/l to 3 mg/l. In both cases, a major impact was observed, the radon apparent specific activities decreasing exponentially with gas concentration. For a CO2 concentration of 1.29 g/l, the apparent specific activity underestimated the true value by 24.5%, while for a concentration of 5.19 g/l CO2 the decrease was of 57%. For H2 S, the radon measured values decreased by 42.5% for concentrations as low as 0.5 mg/l, culminating in a reduction of 86.9% for 3 mg/l H2 S. We are attributing these effects to 218 Po neutralization processes, which reduces the electrostatic efficiency of the silicon detector system. To eliminate the interferences of these gases on RAD7 measurements, a sample preparation method was developed and tested, involving the precipitation and deposition of CO2 using Ca(OH)2, and H2 S using Pb(NO3 )2 .. The findings of the present study clearly indicate that in order to perform valid radon measurements in gas-rich waters with RAD7, the effect of the interfering gases must be considered. Graphical Abstract: ga1 Highlights: Discrepancy between LSC and RAD7 radon measured values in natural spring waters. Influence of variable CO2 and H2 S concentrations on RAD7 measurements in water. Exponential decrease in RAD7 radon measured value correlated to presence of CO2 and H2 S. RAD7 may not be suitable for radon measurements in CO2 and H2 S-rich waters. Precipitation of CO2 and H2 S is used to eliminate interferences on measurements.